DLMA_NEU: Digital Literacy Mobile Application for Children - Nawaila, Muhammad Bello; Kanbul, Sezer; Kani, Umar Mohammed; Magaji, Mohammed Mukhtar (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This paper presents the design and implementation of DLMA_NEU, adigital literacy mobile application for Android that targets children between ages 7 and 18. It is a developmental study aimed at designing a digital literacy mobile application the study conducted in the following three phases: Phase 1. Literature review; mobile application store search, and interviewing experts in children’s digital literacy, Phase 2 Smart phones app development and Phase 3 Accessing the functionality and usability of the app. Thirty students from Near East College and 5 experts were used throughout the research process. The App is the first digital literacy mobile application in Turkish.DLMA_NEUemploys children’s opinions and also adds the interactive option. To use the application, a child is required to register first.And to provide representation, the application currently supports two languages (English and Turkish). The application supports chatting with friends, and educates children (via videos, text, cartoons and jokes) on how to interact online. The application also serves as an avenue for children to report cyber bullying and other online issues as well assimultaneously acquiring informationon internet usage habits. DMLA_NEU is currently at the testing stage by children from TRCN.